Tourist satisfaction towards facilities provided in Melaka heritage sites / Muhammad Izzul Hanis Nazri - Nazri, Muhammad Izzul Hanis (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2015)
The purpose of this paper is to examine tourist satisfaction towards facilities provided in Melaka heritage sites. A total of 200 respondents from tourist in Melaka heritage sites had participated through convenient sampling technique in answering the questionnaires. Most of respondents are male, the age is between 21 — 30 years old. The Cronbach's Alpha result for general facilities, specific facilities and services shows a strong positive relationship which means variables is relevant. For the recommendation,there are some recommendations and suggestions to improve satisfaction of tourist towards facilities provided in Melaka heritage sites. Based on data gather from questionnaires it showed that likers scale for all variables indicate to the 5 which is means slightly satisfy. Thus it is important for the Melaka heritage sites management improve their facilities in order to get the fully satisfaction from the future visitor.